2019
DOI: 10.1158/1538-7445.am2019-3734
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3734: Cancer cell-targeted photoimmunotherapy elicits immunogenic cell death and activates the innate and adaptive immune response in the tumor microenvironment

Abstract: INTRODUCTION: Cancer cell-targeted photoimmunotherapy (PIT) is a platform technology under development for the treatment of various cancers. PIT is a drug + device combination that utilizes monoclonal antibodies conjugated to a dye (IRDye 700DX) that are activated with nonthermal red light illumination to induce rapid cell death by necrosis. Binding of the antibody-dye conjugate to cancer cells followed by photoactivation with nonthermal red light elicits rapid necrosis of the cancer cells bound to the antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In summary, Ru‐GNC‐mediated radiochemotherapy greatly inhibited tumor growth and induced a robust immune response without systemic toxicity. Additionally, we found that tumors in the treatment group exhibited varying degrees of overexpression of PD−L1, with those in the Ru‐GNCs+2 Gy group showing the highest level (Figure 5i and S43) [38] . This laid the groundwork for the subsequent combination of immunotherapy with αPD−L1.…”
Section: Resultsmentioning
confidence: 73%
“…In summary, Ru‐GNC‐mediated radiochemotherapy greatly inhibited tumor growth and induced a robust immune response without systemic toxicity. Additionally, we found that tumors in the treatment group exhibited varying degrees of overexpression of PD−L1, with those in the Ru‐GNCs+2 Gy group showing the highest level (Figure 5i and S43) [38] . This laid the groundwork for the subsequent combination of immunotherapy with αPD−L1.…”
Section: Resultsmentioning
confidence: 73%
“…Additionally, we found that tumors in the treatment group exhibited varying degrees of overexpression of PDÀ L1, with those in the Ru-GNCs + 2 Gy group showing the highest level (Figure 5i and S43). [38] This laid the groundwork for the subsequent combination of immunotherapy with αPDÀ L1.…”
Section: Methodsmentioning
confidence: 98%